(untitled) (American Journal of Islam and Society, 2015)
Jacques Derrida believed that metaphysics in the West has involved installing hierarchies, orders, and binaries in which one party enjoys the presence of a feature that the other party wants. Every succession relies on the idea of originariness, and thus the identity of the latter depends upon the former, for the presence of one element takes priority to its absence. This is how a binary opposition comes to being. Although basing his ideas on Saussure’s philosophy of language, Derrida objected to the latter’s “binary opposition” on the grounds that the interpretations predicated on this thought were called into question because there is no true opposition between a pair of notions. This protest led him to create binary pairs. This article reveals the problems accompanying the conception of the binary pair and offer alternatives. The researcher does not mean to reject the binary pair itself; however, underlining this idea in a way that obstructs other paths will be questioned and some supplementary notions for the binary opposition and binary pair will be proposed.